2021
DOI: 10.1037/stl0000290
|View full text |Cite
|
Sign up to set email alerts
|

Making large classes feel small: An examination of student interactions with undergraduate teaching assistants.

Abstract: The current pattern of class size increases and funding decreases have forced introductory course instructors to develop increasingly creative teaching methods. The use of undergraduate teaching assistants (UTAs) is a viable option, especially if departments lack funding for graduate teaching assistants. According to previous research, the use of UTAs is beneficial for both the students and the UTAs themselves. However, the nature of the direct relationship between students and UTAs is unknown. This project lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Finally, it should be noted that groups can also be established for the exclusive purpose of peer support, rather than to facilitate assignment completion. Previous research on teaching with teams has demonstrated the efficacy of this type of course design (Cavazos, Riggenbach, et al, 2021;Whisenhunt et al, 2019). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Principle 5: Develop Reciprocity and Cooperation Among Studentsmentioning
confidence: 99%
“…Finally, it should be noted that groups can also be established for the exclusive purpose of peer support, rather than to facilitate assignment completion. Previous research on teaching with teams has demonstrated the efficacy of this type of course design (Cavazos, Riggenbach, et al, 2021;Whisenhunt et al, 2019). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Principle 5: Develop Reciprocity and Cooperation Among Studentsmentioning
confidence: 99%
“…Data on the benefits of student participation in peer-facilitated workshops is compelling. PLTL, SI, and UTA experiences are positively associated with course grades (Pennington et al, 2021; Stewart et al, 2007) comprehensive final exam scores (Lewis, 2011), pass rates (Horwitz & Rodger, 2009), retention from one class level to next (Mitchell et al, 2012), and emotional support in challenging classes (Cavazos et al, 2021). Although peer-facilitators may differ in the scope of their responsibilities, the linchpin of students’ success is often the peer-led supplemental workshop and their positive outcomes, which affirm the recommendations made by early progenitors of such programs (Gafney, 2001; Varma-Nelson & Gosser, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In short, to boost performance and interest in psychology, design engagement into the course.Students who feel like outsiders may not be engaged by introductory psychology, so another theme is to foster students' sense of belonging. Like engagement, belonging predicts course performance (Yust et al, 2021), but students vary in how much they connect with their classmates (Cavazos et al, 2021) and some students do not see themselves represented in the science of psychology (Prevatt et al, 2021). Gender and multiculturalism are the two topics most likely to be omitted from the course (Richmond et al, 2021), and that is a missed opportunity to demonstrate the value of diversity in psychology.…”
mentioning
confidence: 99%
“…To help students succeed, introductory psychology teachers can explicitly teach students about effective learning techniques (Richmond et al, 2021) and design their course activities and materials to maximize learning (Altman et al, 2021; Moen, 2021). Also, instructors can connect students to peers, teaching assistants (Cavazos et al, 2021), and learning centers (Grewe et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation